The problems of quality assessment and management of loan portfolio quality. - Almamedova, E. M. (Journal of Economic Research & Business Administration, 2015)
The problems of quality assessment and management of loan portfolio quality. This article considers the problems of quality assessment of the loan portfolio , special attention is given to the factors influencing on the quality of the portfolio. Carrying out credit operations, the bank seeks not only to increase their volume, but also to improve the quality of the loan portfolio. Considered the components that are needed to build an effective system of management of loan portfolio quality. This work describes the significant role of credit policy , since the credit policy is needed inorder to minimize credit risk and increase the quality of the portfolio, considered measures to improve the quality of loan portfolio .Special attention is paid to the problem of overdue debt